LITERATUR REVIEW: SEJARAH KOPERASI DAN IDE-IDE KOPERASI - Ananda, Nadya Asri; Wijaya, Tiara Alfara; Utama, Rony Edward (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This literature review delves into the core issues surrounding the history and ideologies of cooperatives. The primary research focus is to trace the evolutionary path of cooperatives, examining their historical development and underlying ideas. The objective is to provide a comprehensive understanding of the cooperative movement's evolution over time. Employing a literature review methodology, this study analyzes a range of scholarly works, historical documents, and theoretical frameworks. The results highlight significant milestones in the historical evolution of cooperatives, shedding light on the diverse ideologies that have shaped cooperative principles. This research contributes valuable insights to the discourse on cooperatives, emphasizing the importance of historical context and ideological evolution in comprehending the principles that underpin cooperative structures.Keywords : Cooperatives, Historical Evolution, Ideologies, Principles